Navigation in Endoscopic Sinus Surgery: The First Indian Experience - Rai, Devinder (Springer India, 2013)
Although the use of image guidance surgery (IGS) is standard practice in developed countries, it has not been in use in Indian Otolaryngology ever since its clinical inception in 1994. Some clinically interesting applications, relevant indications, practical tips and results in the Indian context are presented. Usage technique and data presentation. Indications based on AAO-HNS 2002 guidelines seem valid, and though the accuracy parameters remain still guarded, in line with the best technology available, based on the evidences of scattered reports and expert opinions, the use of navigation can be recommended as state of the art. IGS provides reliable information to a sinus surgeon in difficult circumstances. Its adaptation fortunately does not require a significant learning curve as it does not change the methodology of the surgical procedure. It can be an excellent teaching tool, but its use does not replace proper surgical training.